(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Encounter killing is a euphemism for extrajudicial executions by Police and Law enforcement agencies in South Asian region including India. This phenomenon presents a profound challenge to the constitutional fabric of India. This paper examines the debate surrounding these killings, which has been positioned between the imperative on the state to maintain law and order and the constitutional obligation of state to uphold the rule of law. The research paper traces the genealogy of encounter killings from their colonial antecedents and use in counter-insurgency to their present-day institutionalization as a tool for routine crime control by employing a qualitative, doctrinal, and comparative methodology. It critical analyses the legal framework including constitutional sanctity of life under Article 21, statutory provisions of private defence and use of force (Sections 34-44 BNS and Section 43 BNSS) which are often invoked as justification. It also evaluates the efficacy of judicial interventions, particularly the landmark 16-point guidelines laid down by the Supreme Court in People’s Union for Civil Liberties v. State of Maharashtra, and the oversight role of the National Human Rights Commission (NHRC). The paper deconstructs the competing narratives of encounters as a “necessary evil” fueled by a failing criminal justice system, and as an “unruly horse” that tramples upon fundamental rights and fosters a culture of impunity. The analysis reveals that the persistence of encounter killings is linked to systematic weaknesses, the lack of political will for police reform and the failure of accountability mechanisms for the cure of which holistic reforms are necessary. The paper concludes by suggesting reforms which aimed at strengthening the rule of law, ensuring police accountability, and realigning policing with democratic and human rights principles.